THE DIVIDEND BASE. - Littleton, A. C. (The Accounting Review, 1934)
Abstract The fault of having two bases for dividend is that they may be considered identical when that is not the case. With two bases in existence the way is opened for creating an excess of assets by revaluation and for paying dividends out of prior profits while allowing revaluation surplus to take the place of the profits withdrawn. Recent experiences have suggested the need for some measure of enlarged control in the public interest over corporation finance and operation. For the most part these control measures have been aimed at the issue of securities, that is, aimed at controlling promotion. But promotion is secondary to the expectation of profits and expectations of future profits rests very largely upon the current and recent past experience in producing profits. It is clear therefore that a sound legal and accounting determination of real profits has much more significance than has the theoretical preservation of a margin for the protection of creditors of a limited liability corporation.